Limitations in evaluating COVID-19 protective face masks using open circuit spirometry systems: respiratory measurement mask introduces bias in breathing pressure and perceived respiratory effort - Seibt, Robert; Bär, Mona; Rieger, Monika A; Steinhilber, Benjamin (Physiological measurement, 2023)
Objective. In response to the COVID-19 pandemic and the resulting widespread use of protective face masks, studies have been and are being conducted to investigate potential side effects of wearing masks on the performance and physiological parameters of wearers. The purpose of the present study is to determine whether and to what extent the use of a respiratory measurement (RM) mask—which is normally used during open-circuit spirometry—influences the results of these types of studies. Approach. 34 subjects were involved in this intra-subject study with a cross-over design. Four different protective face masks, Community Mask, medical Mouth-Nose-Protection Mask, Filtering Face Piece Mask Class 2 (FFP2), and FFP2 with exhalation valve (FFP2ex), were tested at rest and during deep breathing by using or not using a RM mask (RM versus noRM). Breathing pressure inside the protective face masks was measured during inhalation and exhalation, and subjects rated breathing effort using an 11-stage Borg scale. Main results. The use of an additional RM mask—worn over the protective face masks—significantly increased inspiratory pressures under all mask conditions. The respiratory pressure rises to a level that substantially distorts the results. Expiratory pressure was also significantly increased except for the FFP2ex mask condition. The perceived respiratory effort was significantly increased by 1.0 to 2.8 steps on the Borgs scale for all mask conditions compared with noRM. Significance. We strongly recommend avoiding the use of RM masks for evaluating the effects of protective face masks on human physiology and subjective perception.